2021
DOI: 10.1016/j.synbio.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat-resistant β-glucosidase in Escherichia coli and its application in the production of gardenia blue

Abstract: Gardenia blue is a natural blue pigment that is environmentally friendly, non-toxic, and stable. The hydrolysis of geniposide, catalyzed by β-glucosidase, is a critical step in the production process of gardenia blue. However, β-glucosidase is not resistant to high temperatures, limiting the production of gardenia blue. In this study, we investigated the effectiveness of a heat-resistant glucosidase obtained from Thermotoga maritima in the production of gardenia blue. The enzyme exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Recombinant β-glucosidase could be used for preparation of GB by catalyzing the hydrolysis of gardenia glycoside to produce genipin, followed by the reaction of genipin with amino acids, but the reaction efficiency was relatively low, with a reaction time of 8 h at 90°C. Li et al ( 11 ) expressed a heat-resistant β-glucosidase from Thermotoga maritima in E. coli and used it to produce GB. Single-factor and orthogonal analyses showed that exogenously expressed heat-resistant glucosidase reacted with geniposide and glycine at 94.2°C, producing a maximum yield of GB after 156.6 min.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recombinant β-glucosidase could be used for preparation of GB by catalyzing the hydrolysis of gardenia glycoside to produce genipin, followed by the reaction of genipin with amino acids, but the reaction efficiency was relatively low, with a reaction time of 8 h at 90°C. Li et al ( 11 ) expressed a heat-resistant β-glucosidase from Thermotoga maritima in E. coli and used it to produce GB. Single-factor and orthogonal analyses showed that exogenously expressed heat-resistant glucosidase reacted with geniposide and glycine at 94.2°C, producing a maximum yield of GB after 156.6 min.…”
Section: Discussionmentioning
confidence: 99%
“…S1 in the supplemental material). This method provides the GB with a higher level of purity but at a higher cost as well ( 11 ). Glycine, alanine, valine, leucine, and other amino acids can be used to prepare GB, and glycine is one of the most readily available amino acids in molecular laboratories ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GB and GY dyes were obtained from Wuhan Green Food Biological Engineering Co. Ltd. (China). The chemical structures of the main components of MR 34 , GB 35 , 36 , and GY 37 are shown in Fig. 1 .…”
Section: Methodsmentioning
confidence: 99%